Can the self become another? Investigating the effects of self-association with a new facial identity. Issue 6 (3rd June 2017) - Payne, Sophie; Tsakiris, Manos; Maister, Lara
ABSTRACT: The mental representation of the self is a complex construct, comprising both conceptual information and perceptual information regarding the body. Evidence suggests that both the conceptual self-representation and the bodily self-representation are malleable, and that these different aspects of the self are linked. Changes in bodily self-representation appear to affect how the self is conceptualized, but it is unclear whether the opposite relationship is also true: Do changes to the conceptual self-representation affect how the physical self is perceived? First, we adopted a perceptual matching paradigm to establish an association between the self and an unfamiliar face (Experiment 1). Robust attentional and perceptual biases in the processing of this newly self-associated object suggested that the conceptual self-representation was extended to include it. Next, we measured whether the bodily self-representation had correspondingly changed to incorporate the new face (Experiment 2). Participants rated morphs between their own and the newly-associated according to how similar they were to the self, before and after performing the perceptual matching task. Changes to the conceptual self did not have an effect on the bodily self-representation. These results suggest that modulatory links between aspects of the mental self-representation, when focused on the non-social self, are unidirectional and flow in a bottom-up manner.